SKEPTISME PROFESIONAL AUDITOR DALAM MENDETEKSI KECURANGAN - Agung Waluyo (Jurnal Akuntansi Bisnis, 2017)
Professional skepticism is an attitude includes a questioning mind and acritical assessment of audit evidence. Auditors should maintain a certain level ofprofessional skepticism in detecting financial statement fraud since the perpetratorsconceal the resulting irregularities. Two experiments were conducted. First, a 3x3between subjects experiment design was conducted to investigate how fraud riskassessment affect the level of professional skepticism on the different level of trust inauditor-client relationship. Participants were randomly assigned to one of ninecondition. Second, a within subject experiment design was conducted to examines theeffect of personality type on professional skepticism. A total of] 18 junior, senior andsupervisor auditors from public accounting firm participated in the experiment. A totalof 8 participants were discarded because they failed the manipulation check. Ananalysis of variance (ANOVA) was used for data analysis. The results suggest thatauditors with identification based trust in the high fraud risk assessment group weremore skeptical than in the low fraud risk assessment group. While the auditors withcalculus based trust showed no differences in skepticism between the high group andthe low fraud risk assessment group. Auditors with ST (Sensing-Thinking) and NT(Intuitive-Thinking) types of personality more skeptical than other types.Keywords: Professional Skepticism, Trust, Fraud Risk Assessment